2008
DOI: 10.1111/j.1365-2958.2008.06169.x
|View full text |Cite
|
Sign up to set email alerts
|

BslA, a pXO1‐encoded adhesin of Bacillus anthracis

Abstract: SummaryThe Gram-positive pathogen Bacillus anthracis causes anthrax, a fulminant and lethal infection of mammals. Two large virulence plasmids, pXO1 and pXO2, harbour genes required for anthrax pathogenesis and encode secreted toxins or provide for the poly g-D-glutamic acid capsule. In addition to capsule, B. anthracis harbours additional cell wall envelope structures, including the surface layer (S-layer), which is composed of crystalline protein arrays. We sought to identify the B. anthracis envelope factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(126 citation statements)
references
References 57 publications
3
122
0
Order By: Relevance
“…Host cell viability and immune response to B. anthracis infection are complex processes that are dependent on multiple biological variables, including susceptibility to B. anthracis toxins and expression of cell surface receptors. For example, B. anthracis cells express the BslA adhesin that is required for attachment to host cells (Kern and Schneewind, 2008). Compared with the virulent Ames strain, bslA mutants exhibited a marked increase in LD50 and reduced bacterial load in an anthrax guinea pig model, indicating that BslA functions as a surface adhesin for B. anthracis (Kern and Schneewind, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Host cell viability and immune response to B. anthracis infection are complex processes that are dependent on multiple biological variables, including susceptibility to B. anthracis toxins and expression of cell surface receptors. For example, B. anthracis cells express the BslA adhesin that is required for attachment to host cells (Kern and Schneewind, 2008). Compared with the virulent Ames strain, bslA mutants exhibited a marked increase in LD50 and reduced bacterial load in an anthrax guinea pig model, indicating that BslA functions as a surface adhesin for B. anthracis (Kern and Schneewind, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…HF-PS). Recently, it was shown that another SLH-containing surface protein that is encoded on the pathogenicity island of pXO1, BslA, is involved in the attachment of B. anthracis to host cells (22). Thus, it is possible that the HF-PS is involved in localizing important virulence proteins to the bacterial cell surface.…”
mentioning
confidence: 99%
“…Mutants were screened for growth on BHI agar and no growth on BHI-kanamycin agar. All complementation plasmids were derived from pJK4, and the expression of its P spac promoter was induced with 0.1 mM isopropyl-␤-D-thiogalactopyranoside (IPTG) (32). The primers for the amplification and construction of genes and plasmids are listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%